2008
DOI: 10.1143/jpsj.77.111006
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Turbulence

Abstract: The present article reviews the recent developments in the physics of quantum turbulence. Quantum turbulence (QT) was discovered in superfluid 4 He in the 1950s, and the research has tended toward a new direction since the mid 90s. The similarities and differences between quantum and classical turbulence have become an important area of research. QT is comprised of quantized vortices that are definite topological defects, being expected to yield a model of turbulence that is much simpler than the classical mod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
89
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 69 publications
(90 citation statements)
references
References 76 publications
1
89
0
Order By: Relevance
“…Thus, the investigation of QT may lead to a breakthrough in understanding a mystery of nature pondered since the era of da Vinci. There are many related topics not addressed in this article, regarding which we refer the readers to other review articles [15,16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the investigation of QT may lead to a breakthrough in understanding a mystery of nature pondered since the era of da Vinci. There are many related topics not addressed in this article, regarding which we refer the readers to other review articles [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…The present areas of study of QT are [15,16]: the energy spectra and the dissipation mechanism at zero temperature; QT created by vibrating structures; and visualization of QT.…”
Section: Modern Research Trendsmentioning
confidence: 99%
“…quantum turbulence (QT). QT physics, comprising tangled quantized vortices, is an important research topic in lowtemperature physics [8,9]. Stimulated by recent experiments on both superfluid 3 He and superfluid 4 He, where a few similarities have been observed between quantum and classical turbulence [10][11][12][13][14][15][16][17], studies on QT have entered a new stage where one of the main motivations is to investigate the relationship between quantum and classical turbulence.…”
Section: Introductionmentioning
confidence: 99%
“…Next, the DG instability is microscopically discussed in atomic BECs with the Gross-Pitaevskii (GP) and the Bogoliubov-de Gennes (BdG) models. Finally, it is shown that the DG instability can be applied to the observation of the dispersion relation of Kelvin waves, vortex reconnections [6], and quantum turbulence [7,8] in atomic BECs.…”
Section: Introductionmentioning
confidence: 99%